1996
DOI: 10.1038/ki.1996.493
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic collapsing focal segmental glomerulosclerosis: A clinicopathologic study

Abstract: A review of all native kidney biopsies at our center from 1974 to 1993 identified 43 cases of idiopathic focal segmental glomerulosclerosis (FSGS) with predominantly collapsing features and lacking evidence of HIV-1 infection or intravenous drug use. No case was identified before 1979 and the incidence of this entity has progressively increased over the past two decades. Compared to 50 age-matched controls of idiopathic FSGS with typical perihilar scars, the group of idiopathic collapsing FSGS displayed black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
245
5
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(275 citation statements)
references
References 36 publications
21
245
5
4
Order By: Relevance
“…The FSGS-CT findings support significant differences in demographic features between histologic subtypes. Tip and collapsing variants were more common in teenagers and adults than children (5,6,12,(14)(15)(16)(17)(18)(19). Only 29% of tip patients were children aged 2-12 years at onset of FSGS, whereas 43% were over 18 years.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The FSGS-CT findings support significant differences in demographic features between histologic subtypes. Tip and collapsing variants were more common in teenagers and adults than children (5,6,12,(14)(15)(16)(17)(18)(19). Only 29% of tip patients were children aged 2-12 years at onset of FSGS, whereas 43% were over 18 years.…”
Section: Discussionmentioning
confidence: 96%
“…These variants include the common generic NOS type, the aggressive collapsing type, the abruptly presenting tip type, the early-stage cellular type, and the perihilar type common in secondary adaptive FSGS (13)(14)(15)(16)(17). Several retrospective series have suggested that FSGS histologic subtypes vary in incidence and correlate with remission status and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal CG in autoimmune diseases including SLE, SLE-like disease, and mixed connective tissue disease has been previously reported (1,2,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The aim of this study is to report an analysis of the clinicopathologic findings and the possible association of renal lesions with CG in the setting of SLE and lupuslike disease and review the literature of the reported cases.…”
Section: Introductionmentioning
confidence: 99%
“…The pathologic appearance is characterized by global or segmental collapse of the glomerular capillary tuft, with wrinkling and retraction of the capillary walls overlaid by epithelial cell proliferation in the Bowman space that is frequently accompanied by tubulointerstitial disease (1)(2)(3). CG is regarded as a podocytopathy, it is predominantly seen in the primary form in patients of African descent, and it has been associated with numerous etiologies, including viral infections (HIV, cytomegalovirus, Parvovirus B19, and hepatitis C virus), drugs (pamidronate and all forms of IFN), and anecdotally, autoimmune diseases (SLE and mixed connective tissue disease) (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Collapsing FSGS was mainly described in patients with HIV-associated nephropathy (HIVAN) (13) but also was recognized as a variant of idiopathic FSGS (11,12). Both idiopathic collapsing FSGS and HIVAN are most commonly seen in young black patients (8 -12,14).…”
mentioning
confidence: 99%